Baumol's cost-disease, efficiency, and productivity in the performing arts: An analysis of German public theaters - Anne-Kathrin Last; Heike Wetzel (Leuphana Universität Lüneburg, Institut für Volkswirtschaftslehre, 2010)
This paper analyzes the productivity development in the German public theater sector for the seasons 1991/1992-2005/2006. Using a stochastic distance frontier approach that allows to decompose total factor productivity change into different sources we examine (a) whether Baumol's cost-disease hypothesis is valid in this sector and (b) if so, whether its negative influence on productivity can be compensated by efficiency gains. The findings indicate an increase in real unit labor cost as a result of rising wage rates and, thus, support the cost- disease hypothesis. Furthermore, increasing returns to scale are observed for the majority of the theaters which implies that significant efficiency gains can be realized by the exploitation of scale economies. However, because of the increasing unit labor cost and an increasing scale inefficiency we find an overall decrease in average productivity of about 8 percent within the sample period.
Keywords: D24; O12; Z10; 330; public theaters; cost-disease; efficiency; stochastic frontier analysis; Theater; Produktivität; Wirtschaftliche Effizienz; Technische Effizienz; Lohnstückkosten; Schätzung; Deutschland